PEMBERDAYAAN KELOMPOK TANI HARAPAN JAYA (KTHJ) MELALUI TEKNOLOGI PENGEMASAN INOVATIF UNTUK PRODUK HASIL PERTANIAN - Cindy Malinda Uscha; Dewi Hajar; Ely Rosita (Jurnal Abdi Insani, 2025)
This community service program was designed to empower the Kelompok Tani Harapan Jaya (KTHJ) in Sukawali Village through the application of innovative packaging technology aimed at enhancing the added value of agricultural products. The main challenge faced by KTHJ is the limited shelf life, low quality, and weak competitiveness of horticultural products due to the use of simple packaging that does not align with modern market standards. The program was implemented through six key stages: problem identification, situational analysis, preparation, technology implementation, mentoring and monitoring, and sustainability planning. Activities were conducted on September 18, 2025, in the form of socialization and training, involving 20 members of KTHJ as direct beneficiaries. The outcomes demonstrate a significant increase in farmers’ knowledge and skills related to packaging materials, labeling techniques, and product quality standards. Pretest and posttest results revealed an improvement in packaging understanding from an average of 43.75% to 85.63%. This finding highlights the previous gap in farmers’ access to packaging technology knowledge and training. Furthermore, the establishment of a dedicated packaging unit within KTHJ provides a mechanism to manage packaging material inventory, monitor product quality, and coordinate marketing strategies. This unit ensures program sustainability and continuous benefits for the farmers’ group. Overall, the program successfully strengthened farmers’ capacity to improve product value and competitiveness in the agricultural supply chain.